2018
DOI: 10.1111/cns.13001
|View full text |Cite
|
Sign up to set email alerts
|

Social decision making in autism: On the impact of mirror neurons, motor control, and imitative behaviors

Abstract: SummaryThe Mirror Neuron System (MNS) plays a crucial role in action perception and imitative behavior, which is suggested to be impaired in Autism Spectrum Disorders (ASDs). In this review, we discuss the plausibility and empirical evidence of a neural interaction between the MNS, action perception, empathy, imitative behavior, and their impact on social decision making in ASDs. To date, there is no consensus regarding a particular theory in ASDs and its underlying mechanisms. Some theories have completely fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 74 publications
(105 reference statements)
0
37
0
4
Order By: Relevance
“…Two brain systems (the mirror and the mentalizing systems) are thought to be involved in the processing of understanding intention (Ciaramidaro et al., 2014). Khalil et al. (2018) suggested a multilayer neural network model including the mirror neuron system (MNS) on a first layer and transforming this information to a higher layer network responsible for reasoning.…”
Section: Discussionmentioning
confidence: 99%
“…Two brain systems (the mirror and the mentalizing systems) are thought to be involved in the processing of understanding intention (Ciaramidaro et al., 2014). Khalil et al. (2018) suggested a multilayer neural network model including the mirror neuron system (MNS) on a first layer and transforming this information to a higher layer network responsible for reasoning.…”
Section: Discussionmentioning
confidence: 99%
“…Autism is a highly diverse and heterogeneous spectrum of developmental disorders that are broadly characterized by impaired social interaction and communication. Numerous cognitive theories have been developed to explain the pathogenesis of autism, and these include low-level visual processing 59 and mirror neurons 60 through to predictive coding 61 . An SC theory of autism draws from the wealth of evidence for disrupted or altered SC functioning in attention and face processing, as well as parallels between neural visual development and the onset of autism.…”
Section: Autismmentioning
confidence: 99%
“…Previous studies have uncovered the genetic link between TBR1 and increased risk for ASD (53,62). At the behavioral level, several studies have found VMI deficits (22,63,64) and motor impairment in individuals presenting with ASD (65,66). It is likely that the high expression of TBR1 in the VMI network may result in neuronal changes impacting its functionality, conferring prototypic behavioral phenotypes in ASD individuals.…”
Section: Discussionmentioning
confidence: 99%